GENETIC VARIABILITY OF THREE POPULATIONS OF FLYING FISH, Hirundichthy oxycephalus FROM MAKASSAR STRAIT - Andi Parenrengi; Andi Tenriulo; Syamsul Alam Ali (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Flying fish, Hirundichthy oxycephalus is one of economically important marine species to Indonesia, particularly in Makassar Strait and Flores Sea. However, there is a limited published data on genetic variation in molecular marker level of this species. Random Amplified Polymorphic DNA (RAPD) was employed in this study to determine the genetic variability of three populations of flying fish collected from Takalar, Pare-Pare, and Majene in Makassar Strait. Genomic DNA was isolated from preserved muscle tissue using phenol-chloroform technique. Two selected arbitrary primers (CA-01 and P-40) were performed to generate RAPD finger printing of flying fish populations. The two primers generated a total of 81 fragments (loci) and 50 polymorphic fragments with size ranging from 125 to 1,250 bp. There were no significant differences in number of fragment and number of polymorphic fragment among populations. The high polymorphism (63.5±7.4%) was obtained from Takalar population followed by Pare-Pare (58.3±19.6%) and Majene population (57.7±0.8%). Similarity index of individuals was 0.60±0.17 for Takalar, 0.63±0.17 for Majene and 0.75±0.21 for Pare-Pare population. Seven fragments were identified as species-specific markers of H. oxycephalus. The UPGMA cluster analysis showed that the Takalar population was genetically closer to Pare-Pare population (D= 0.0812) than to Majene population (D= 0.1873).